Influence of the Crystallinity of Silver Nanoparticles on Their Magnetic Properties. Issue 3 (31st January 2023) - Lin, Long; Peng, Xiaogang; Voirin, Emilie; Donnio, Bertrand; Rastei, Mircea V.; Vileno, Bertrand; Gallani, Jean‐Louis
Abstract: The magnetic properties of noble‐metal nanoparticles are a puzzling phenomenon, tentatively often explained as a size effect or a ligand effect. Many experimental studies performed to date have attempted to vary these readily available parameters without reaching a definitive conclusion. In an attempt at better understanding the role of core crystallinity on these magnetic properties, we have compared the behavior of silver nanoparticles, which were either single‐crystalline or multi‐twinned, of almost identical sizes and with the same ligand coating. Our results indicate that single‐crystalline nanoparticles tend to behave as classical paramagnetic materials, whereas multi‐twinned ones exhibit a combination of para‐ and ferro‐magnetic behaviors. Our hypothesis is that lattice defects within the core bear magnetic moments which couple through conduction electrons, with dipolar interactions also playing a local and macroscopic role. Abstract :